2018
DOI: 10.37249/as-salam.v2i2.29
|View full text |Cite
|
Sign up to set email alerts
|

Bahasa Figuratif Dalam Novel Terjemahan Bahasa Inggris Ke Bahasa Indonesia (Suatu Analisis Kesepadanan Terjemahan)

Abstract: Penelitian ini menguraikan penerjemahan kata figuratif dari bahasa Inggris ke dalam bahasa Indonesia yang terdapat pada kidung dan surat-surat dalam novel Lisa See yang berjudul “Snow Flower and the Secret Fan”, strategi yang digunakan penerjemah dalam menerjemahkan kata figuratif yang terdapat di dalam novel, kesepadanan penerjemahan, dan masalah-masalah yang terdapat pada terjemahan yang tidak sepadan serta strategi yang dapat digunakan sebagai solusi untuk mencapai kesepadanan makna di tingkat leksikal pada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Adjustments were made by shifting the structure, changing the point of view, implicit and explicit about the information in it, as well as free translation while still paying attention to the keywords and their stylistic effects. Rakhmyta (2018) described the level of equivalence of the translation results in a literary text. The results showed that literal translation was used by the translator more often than Larson's strategy, which was 49 out of 82 figurative word data.…”
Section: Introductionmentioning
confidence: 99%
“…Adjustments were made by shifting the structure, changing the point of view, implicit and explicit about the information in it, as well as free translation while still paying attention to the keywords and their stylistic effects. Rakhmyta (2018) described the level of equivalence of the translation results in a literary text. The results showed that literal translation was used by the translator more often than Larson's strategy, which was 49 out of 82 figurative word data.…”
Section: Introductionmentioning
confidence: 99%